Implementasi Asesmen Proses di Pendidikan Anak Usia Dini Al-Islam Riyadhul Irfan Kecamatan Kadungora - Siti Aliyah; Ade Rosita; Nova Nurul Huda (LP2M STAI Al-Musaddadiyah Garut, 2026)
Law Number 20 of 2003 concerning the National Education System, Article 1 paragraph 14 states that Early Childhood Education (PAUD) is